Buccal fat pad excision for aesthetic recontouring of the face: a narrative literature review (Research, Society and Development, 2022)
Located in the middle facial third, the buccal fat pad is a biconvex, rounded fat structure limited by a thin capsule. People with an excessive volume of the buccal fat pad may present either a childlike or overweight appearance; however, the surgical excision can sculpt the facial angles and improve facial aesthetics. Although this procedure (also called “bichectomy”) has become so popular nowadays, evidence and studies that provide guidelines concerning technical details are quite limited. Thus, this narrative literature review aimed to summarize as much information as possible regarding the excision of the buccal fat pad for aesthetic recontouring of the face. According to the studies evaluated, the surgical management of the buccal fat pad is considered a relatively simple procedure that presents excellent aesthetic results when properly indicated and performed by a professional experienced in the technique. However, considering the lack of high-level scientific evidence with regards mainly the long-term effects, well-designed studies with appropriate follow-up are still necessary for further clarification and, then, support the technique in the clinical routine.